Keterampilan Mengajar Guru PAK Sebagai Faktor Dalam Menumbuhkan Minat Belajar Siswa di Kelas - Adi Suhenra Sigiro (Sekolah Tinggi Teologi Baptis Medan, 2022)
AbstractThe teacher is an important component in the learning process. As a teacher, teachers must have adequate teaching skills because teaching skills greatly affect students' interest in learning. But in fact, there are still teachers who do not have adequate skills so that it reduces students' interest in taking lessons. Students sometimes feel bored and bored because the teacher has not been able to apply teaching skills optimally. The research method used is library research. This method collects data and information in the form of documents, data archives and other literature information. The author will take a descriptive approach to describe the information that the author finds in accordance with the research topic. The analysis process is carried out using various sources of literature, both journals, books and other reference materials to support the author's analysis of the research topic. This study aims to increase the understanding and insight of teachers in applying various teaching skills so that they can foster student interest in learning. The teaching skills that must be mastered by teachers so that they can increase students' interest in learning are as follows, namely the teacher must have the skills to open and close lessons, ask questions, explain skills, make variations, manage classes, lead group discussions, and provide reinforcement skills. Keywords: teaching skills, teachers, interest in learning, students